Using the Critical Path Method (CPM) for scheduling the project (paving the Amil Sayid Al-Ayyam Street with a length of 1.25 km) In terms of Decresing the time - جواد, مها كامل; كاظم, علي جواد (Journal of Economics and Administrative Sciences, 2020)
The implementation of the concept of project scheduling in the organizations generally requires a set of procedures and requirements, So, most important of all is the understanding and knowledge of the tools and techniques which are called the methods of scheduling projects. Consequently, the projects of the municipality administration in the holy governorate of Karbala suffer from the problem of delaying their projects and chaos in the ways of implementation. To provide assistance to this directorate and to demonstrate how to schedule projects using one of the advanced scientific methods that proved their ability to schedule any project and its potential to accelerate the time of completion, as well as ease of use and effectiveness of the results, especially with the introduction of software programs. The study concluded with a number of conclusions, including the delay of most of the projects for their specific times for several reasons, the most important of which is the lack of good planning and scheduling suitable to increase the number and variety of projects, as well as the possibility of reducing the time of completion of the project, And the most important recommendations of the research urged the departments of the municipality and government agencies and committees to prepare the drafts of guessing projects, as well as the companies and contractors, using modern methods and software in the scheduling of projects, and control the time in planning and scheduling projects to ensure that not delayed Properly on time.